A novel cold‐sensitive mutant of ntla reveals temporal roles of brachyury in zebrafish. Issue 8 (27th May 2016) - Kimelman, David
Abstract : Background : With the exception of the head, the vertebrate embryonic body is formed progressively in an anterior‐posterior direction, originating from a posteriorly located bipotential neural‐mesodermal progenitor population. The T‐box transcription factor Brachyury is expressed within the progenitors and is essential for the formation of the posterior mesoderm. A novel cold‐sensitive mutant of Zebrafish Brachyury ( ntla cs ) is described that allows exploration of the temporal role of this key factor.Results : The ntla cs mutant is used to show that Ntla has an essential role during early gastrulation, but as gastrulation proceeds the importance of Ntla declines as Ntlb acquires a capacity to form the posterior mesoderm. Remarkably, ntla cs embryos held at the nonpermissive temperature just during the gastrula stages show recovery of normal levels of mesodermal gene expression, demonstrating the plasticity of the posterior progenitors.Conclusion : ntla cs is a valuable tool for exploring the processes forming the posterior body since it allows temporally specific activation and inactivation of Brachyury function. It is used here to show the changing roles of Ntla during early development and the dynamics of the neuromesodermal progenitors. Developmental Dynamics 245:874–880, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: A novel cold‐sensitive mutant of zebrafish brachyury (ntla) is described. The time‐dependent roles of ntla during early zebrafish development is elucidated. This study shows the plasticity of the bipotent neuromesodermal progenitors that form the posterior embryonic body.